Mega damages award on defamation suit in Malaysia: is it reasonable? / Ainul Hafiza Zainudin, Mohd Munzil Muhamad and Nurulhuda Mohd Maarof. - Zainudin, Ainul Hafiza; Muhamad, Mohd Munzil; Mohd Maarof, Nurulhuda (2006)
This thesis deals with the law of defamation in Malaysia. It concerns with the area of damages granted by the court in the defamation suit. The main intention of this research is to make a fair comparison whether it is reasonable or not to grant mega damages award in defamation suit. However, the position of our court is split into two different views whereby each of them has a very strong basis on this issue. The former view is in favour of mega damages as it is proportionate in comparison with what had been done to Plaintiffs reputation. However, the later view argue that mega damages granted would only amount to some oppression to freedom of expression and setting to stop the trend of mega damages award. Besides that, this research will also look into the quantum of damages granted by the court since in 1970's up until the day this research is written. In addition, a brief comparison with the cases in United Kingdom is made in order to determine the position upheld by the court with regard to mega damages in defamation suit. Furthermore, a detailed discussion will be explained on the factors that would be put into consideration by the court when granting the damages to the plaintiff. The methodology used in this research is basically divided into three forms. Cases review is the paramount methodology in this research since it determines to understand the position of the court on the issue of mega damages in defamation suit. Interviews and library search are the other two important methodologies used in this research. The materials used in this research are mainly case laws, textbooks, articles and statutes.